A escrevivência de Bianca Santana como (re)existência ao racismo em Quando me descobri negra - Sousa, Sílvia Teixeira de (2024)
This dissertation discusses the escrevivência of the writer Bianca Santana in her book “Quando me descobri negra” (2015) as a form of (re)existence against racism. The study encompasses the journey of racial self-discovery of the writer, connecting it to other research that exposes similar narratives of black individuals seeking to understand their racial identity. It aims to deepen the understanding of the experiences lived by Bianca Santana, through her “escrevivência”, encompassing the traumas resulting from her experiences in a silenced space and exploring how literary expression becomes a form of (re)existence against racism. Based on the narratives present in “Quando me descobri negra”, we analyze the environments in which racism is nurtured, such as everyday circumstances within the family, school, and workplace, aiming to trace the path through which Bianca Santana navigates until fully embracing her black identity. Thus, a dialogue is promoted in which the perception of black identity is formed through a process that is subject to evolution and changes. Within this context of the socio-cultural elaboration of the writer’s identity, she acknowledges her blackness and, at the same time, understands herself as a political subject destinded to confront the persistent presence of racism in our society, often masked by the notion of racial democracy. One way to combat racism is to assume the role of protagonist of one’s own story, shaping one’s own reality through “escrevivência”. Therefore, the theoretical framework for the foundation of this research is the studies by Conceição Evaristo (2005, 2009, 2020) concerning the experience of “escrevivência” of black women who produce texts facing the intersection of gender, class, and racial oppressions. Thus, it is demonstrated that these individuals challenge forms of discrimination by constructing their own subjectivities. As a result of the study, it is argued that “escrevivência” constructs subjects capable of opposing racist and oppressive colonial logic. That is, “escrevivência” promotes the construction of a narrative of (re)existence. For this purpose, the theoretical foundation of this work is also based on the academic contributions of Carneiro (2005), Gonzalez (1982, 2018, 2020), Nascimento (2015, 2022), Santana (2020) and Sousa (1983), along with the works of Fanon (2008), Kilomba (2009), and Mbembe (2014), among others committed to racial issues.